Analytic Mapping Associated with Generalized Modular Equation - Alam, Md Shafiul (GANIT: Journal of Bangladesh Mathematical Society, 2024)
Abstract available in PDF GANIT J. Bangladesh Math. Soc. 44.1 (2024) 77–91